How to violate the first law of thermodynamics with an ASE of Papain and Newcomen before it was stated by Clausius (JOURNAL OF ADVANCES IN PHYSICS, 2025)
This paper explores the historical and thermodynamic implications of the atmospheric steam engines (ASE) developed by Denis Papin and Thomas Newcomen in the late 17th and early 18th centuries. These engines, which operated using vacuum-induced contraction rather than steam expansion, seemingly violated the first law of thermodynamics—conservation of energy—before it was formally articulated by Rudolf Clausius in the mid-19th century. Papin's innovative approach utilized thermal contraction and atmospheric pressure to perform mechanical work, a method later refined by Newcomen. The engines achieved work through vacuum generation by condensing steam with cold water, a process that contradicted the conventional understanding of energy conservation as later defined by Clausius and Carnot. The paper analyzes the operational principles of Papin’s and Newcomen’s ASEs, highlighting how their contraction-based work led to an increase in internal energy while performing useful mechanical work, a phenomenon inconsistent with the first law of thermodynamics. The study also examines the transition from contraction-based engines to expansion-based systems, such as the Rankine cycle, and discusses the implications of these early engines on the development of thermodynamic theory. Through case studies and experimental evidence, the paper argues that the first law, as originally stated, fails to account for contraction-based work, suggesting a need for its revision to include such phenomena. The findings underscore the historical significance of Papin’s and Newcomen’s contributions to engineering and thermodynamics, while also raising questions about the completeness of classical thermodynamic principles.